Why is dairy production so difficult to stabilize? Research on the micro-mechanism and transformation mechanism of cyclical fluctuations of raw milk prices in China - Hua, Junguo; Ma, Chunhui; Kang, Yu; Jia, Yunfei (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe cyclical fluctuations characterized by drastic ups and downs in raw milk prices have long been one of the bottlenecks restricting the high-quality development of the Chinese dairy industry.MethodsTo clarify the formation rule of the cyclical fluctuations of raw milk prices in China, this study deeply analyzed the internal mechanism of the periodic fluctuations in raw milk prices from a microscopic perspective. Utilizing price index data from November 2007 to August 2024, we used a two-threshold mechanism transfer model to research the transformation mechanism and duration of the periodic fluctuations in raw milk prices.Results and discussionThe findings indicated that raw milk price fluctuations exhibit nonlinear mechanism transformations at two critical thresholds: a price index of 107.74 (which reflects an approximate increase of 8% after adjusting for seasonal and pricing factors) and a change rate in the price index of 0.016 (approximately 0). A complete price fluctuation cycle of raw milk comprises four phases: the low-price uptrend phase, the high-price uptrend phase, the high-price downtrend phase, and the low-price downtrend phase. Among these phases, the duration of the upward phases is generally longer than that of the downward phases; the duration of the high-price uptrend phase and the low-price downtrend phase exceeds that of the low-price uptrend phase and the high-price downtrend phase, respectively. Hence, relevant policy suggestions are put forward from four main aspects: strengthening source governance, improving the regulatory mechanism, building an early warning system, and establishing a purchase and storage system.